2005
DOI: 10.1007/s00125-004-1632-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of subclinical diabetic heart disease

Abstract: Aims/hypothesis: Subclinical left ventricular (LV) dysfunction has been shown by tissue Doppler and strain imaging in diabetic patients in the absence of coronary disease or LV hypertrophy, but the prevalence and aetiology of this finding remain unclear. This study sought to identify the prevalence and the determinants of subclinical diabetic heart disease. Methods: A group of 219 unselected patients with type 2 diabetes without known cardiac disease underwent resting and stress echocardiography. After exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 36 publications
10
97
2
7
Order By: Relevance
“…Consistent with other published studies, 3,4,[13][14][15] our study demonstrated that patients with type 2 diabetes mellitus have impaired LV systolic and diastolic function despite a normal LV ejection fraction. Our study also showed that better glycemic control over a 12-month period resulted in improvements in LV systolic and diastolic function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other published studies, 3,4,[13][14][15] our study demonstrated that patients with type 2 diabetes mellitus have impaired LV systolic and diastolic function despite a normal LV ejection fraction. Our study also showed that better glycemic control over a 12-month period resulted in improvements in LV systolic and diastolic function.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have shown that poor glycemic control was associated with abnormal LV relaxation, elevated LV filling pressures, and lower systolic strain. 13,19,20 Patients who had poorly controlled diabetes mellitus in the Strong Heart Study were found to have abnormal LV relaxation. 20 In 120 patients with type 2 diabetes mellitus after exclusion of ischemia and LV hypertrophy, peak systolic strain was independently associated with HbA1c levels, whereas septal e′ velocities were more related to age and hypertension but not related to glycemic control.…”
Section: Systolic and Diastolic Function In Diabetes Mellitusmentioning
confidence: 99%
“…24) Briefly, an exercise induced increase in the E/e' ratio seems to be a good predictor of reduced ventricular compliance and decreased exercise capacity. 25) Due to direct metabolic effects on myocytes, 26) and disturbances in the microvascular function 27) and autonomic neuropathy; 28) myocardial dysfunction is a common involvement in T2DM. 29) Diastolic dysfunction is the earliest manifestation of diabetic cardiomyopathy and even a small amount is a predictor of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, although pioglitazone improved cardiac function in experimental diabetic cardiomyopathy, 13,14 its use in patients may result in heart failure due to fluid retention. 15 Inasmuch as the majority of patients in the PROactive study had CAD and longstanding diabetes, it is feasible that cardiac inability to accommodate metabolic changes may have contributed to the pioglitazone-related heart failures. Indeed, substrate manipulation in heart failure due to CAD decreased myocardial efficiency and cardiac function, 16 which reveals the close connection of metabolism and function in the compromised heart.…”
Section: Editorial P 2020 Clinical Perspective P 2077mentioning
confidence: 99%